PELAKSANAAN PEMBELAJARAN SEJARAH PADA PROGRAM 4 SEMESTER - Wulandari, Esti; Agung S, Leo; Yuniyanto, Tri (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
The purposes of this study were to determine (1) planning of history learning in 4 semesters program at SMA N 3 Surakarta; (2) describe the teaching learning process of history lesson in 4 semesters program at SMA N 3 Surakarta; (3) problems faced by the teacher in teaching learning process of history lesson in 4 semesters program; (4) solutions to resolve the problems faced by the teacher inteaching learning process of history lesson in 4 semesters program at SMA N 3 Surakarta.This study used descriptive qualitative method. Data were collected through observation, interview, and document analysis. Data validity was done through method triangulation and source triangulation. Technique of analyzing data used by the author was an interactive model of analysis that includes data reduction, data presentation and drawing conclusions or verification. The result of this research showed that (1) teacher used the same planning of history learning with regular class, but the time allocation in teaching learning was different; (2) The strategies in teaching learning process in four semesters program are faster than regular class; (3) There are two factors that being problems faced by the teacher in teaching learning process of history lesson in four semesters program. The first, the differences of students concentration level in material include in internal factors. Second, the time allocation was given by the school demanded faster than regular class include in external factors; (4)To resolve the problems faced in teaching learning process, the teacher used some strategies to attract the students? concentration. For example, the teacher devided the material into several forms.